Rangewide habitat suitability analysis for the Mexican wolf (Canis lupus baileyi) to identify recovery areas in its historical distribution. Issue 4 (21st January 2021) - Martínez‐Meyer, Enrique; González‐Bernal, Alejandro; Velasco, Julián A.; Swetnam, Tyson L.; González‐Saucedo, Zaira Y.; Servín, Jorge; López‐González, Carlos A.; Oakleaf, John K.; Liley, Stewart; Heffelfinger, James R.
Abstract: Aim: To develop an updated distribution model and habitat suitability analysis for the Mexican wolf, to inform the recovery efforts in Mexico and the United States. Location: Mexico and the southwestern United States. Methods: We used an ensemble species distribution modelling (SDM) approach and a spatial analysis combining anthropogenic and ecological variables, including, for the first time, rangewide relative density estimates of wild ungulates, to determine the extent of suitable habitat for wolves within a region that includes the known historical range of the Mexican wolf and adjacent areas. Results: The results showed that the modelled distribution of the Mexican wolf extended from central Arizona and New Mexico, and western Texas in the United States, southwards along the Sierra Madre Occidental and the Sierra Madre Oriental, to the high sierras of Oaxaca, in Mexico. The habitat suitability models indicated that large tracts (>81, 000 km 2 ) of high‐quality habitat still exist for the Mexican wolf in the southwestern United States, and the Sierra Madre Occidental and the Sierra Madre Oriental in Mexico, which could ensure recovery within its historical range. Main conclusions: The recovery of the Mexican wolf is a complex, multidimensional socio‐ecological challenge, which requires binational cooperation guided by reliable information and robust scientific procedures. The next step is to carry out specific socio‐ecological studies and actions for selected candidate sites to assess their viability for hastening its recovery.